Parkia speciosa Hassk.: A Potential Phytomedicine. (16th July 2013) - Kamisah, Yusof; Othman, Faizah; Qodriyah, Hj Mohd Saad; Jaarin, Kamsiah
Abstract : Parkia speciosa Hassk., or stink bean, is a plant indigenous to Southeast Asia. It is consumed either raw or cooked. It has been used in folk medicine to treat diabetes, hypertension, and kidney problems. It contains minerals and vitamins. It displays many beneficial properties. Its extracts from the empty pods and seeds have a high content of total polyphenol, phytosterol, and flavonoids. It demonstrates a good antioxidant activity. Its hypoglycemic effect is reported to be attributable to the presence of β -sitosterol, stigmasterol, and stigmast-4-en-3-one. The cyclic polysulfide compounds exhibit antibacterial activity, while thiazolidine-4-carboxylic acid possesses anticancer property. The pharmacological properties of the plant extract are described in this review. With ongoing research conducted on the plant extracts, Parkia speciosa has a potential to be developed as a phytomedicine.